Pengaruh Pabrik Gula PTPN VII Terhadap Ekonomi dan Kesejahteraan Petani Binaan Desa Sukamaju Kecamatan Bunga Mayang Kabupaten Lampung Utara Pada Tahun 2013-2018 - Rini Usniatuti; Ali Imron; Yustika Sri Ekwandari (University of Lampung, 2021)
Abstract: The Influence of Ptpn VII Sugar Factory on the Economy and Welfare of Fostered Farmers in Sukamaju Village, Bunga Mayang District, North Lampung Regency in 2013-2018. The research objective was to determine the effect of the PTPN VII Sugar Factory on the economy and welfare of the assisted farmers in Sukamaju Village, Bunga Mayang District in 2013-2018. Using descriptive methods with interview data collection techniques, and documentation. The data analysis technique used is data reduction and data presentation. The results of the analysis and discussion show that the carrying capacity directly opens up employment in improving the farmer's economy, seen from the level of education, health, housing, and developing living facilities, the inhibitory power directly in the efficiency level of the sugar factory stopping the work of the milling machine affects the sugar production. The support capacity, indirectly, the provision of bank loan capital partnered by the sugar factory, as well as the inhibition capacity of the resulting low yield, indirectly, has not been able to reach the benchmark of the Indonesian Sugar Association of 9.00%. Keywords: Economy, Farmers, and Influence